Expression of CD56 is a risk factor for acute lymphocytic leukemia with central nervous system involvement in adults. Issue 2 (7th February 2017) - Hu, Wangqiang; Wang, Xiaoxia; Yang, Rongrong; Bi, Laixi; Xie, Yaosheng; Zhang, Zhuo; Lu, Hong; Wu, Lianfeng
ABSTRACT: Objective: To gain further insights into the predisposing risk factors for central nervous system (CNS) involvement in patients with acute lymphocytic leukemia (ALL), the impact of CD56 expression in these patients was investigated. Methods: We reviewed the clinical features of CD56 expression in 588 consecutive ALL patients treated with systemic chemotherapy regimens between 2000 and 2014. The categorical data from CD56 + ALL patients were compared with those from CD56 − ALL patients. Results: Among the 588 patients studied, 18.9% showed CD56 expression. The expression was significantly associated with CD33 +, CD10 −, CD15 +, TdT −, and CD5 + immunophenotypes. After systemic chemotherapy, 8.8% patients showed CNS involvement, of which 3.2% exhibited combined recurrences and 5.6% exhibited isolated CNS involvement. The 5-year event-free survival was significantly lower for patients with CD56 + immunophenotype compared with patients with CD56 − immunophenotype (22.5% vs. 32.7%, P  = 0.04). Cumulative incidences of CNS involvement were significantly greater in the CD56 + cohort compared with the CD56 − cohort (14.4% vs. 7.5%, P  = 0.02). Multivariate analysis revealed CD56 expression to be statistically significant risk factors for CNS involvement. Conclusion: CD56 expression should be regarded as an independent risk factor for ALL with CNS involvement in adults.